The survivor eaudiobook - Flynn, Vince (Mitch Rapp, 2015)
The #1 New York Times bestselling novel that picks up where the "tight, right, and dynamite" ( Star Tribune , Minneapolis) The Last Man left off, The Survivor is a no-holds-barred race to save America...and Mitch Rapp's finest battle. When Joe "Rick" Rickman, former golden boy of the CIA, steals a massive amount of the Agency's most classified documents in an elaborate betrayal of his country, CIA director Irene Kennedy has no choice but to send her most dangerous weapon after him: elite covert operative Mitch Rapp. Rapp quickly dispatches with the traitor, but Rickman proves to be a deadly threat to America even from beyond the grave. In fact, mysterious tip-offs are appearing all over the world, linking to the potentially devastating data that Rickman managed to store somewhere only he knew. It's a deadly race to the finish as both the Pakistanis and the Americans search desperately for Rickman's accomplices, and for the confidential documents they are slowly leaking to the world. To save his country from being held hostage to a country set on becoming the world's newest nuclear superpower, Mitch Rapp must outrun, outthink, and outgun his deadliest enemies yet in this heart-pounding adventure that proves that Vince Flynn "is a master—maybe the master—of thrillers in which the pages seem to turn themselves" ( Bookreporter ).